Microstructural evolution, thermal stability and nanoindentation behaviour of (MgAl)70Zn20(BiSn)10 light weight high entropy alloy - Henil Thakkar; Sai Sri Harsha G．V; Renuga Devi K; Sreekanth Dondapati (Results in Engineering)
This study investigates the mechanical, microstructural and corrosion behaviour of the (MgAl)70Zn20(BiSn)10 (at.%) high-entropy alloy. X-ray diffraction (XRD)and scanning electron microscopy (SEM) analyses revealed the presence of multiple intermetallics, including Mg2Sn, BCC Bergman phase τ-Mg32(Zn,Al)49, Sn3Bi, Zn2Sn, and Mg3Bi2 in the alloy's microstructure. Compression testing demonstrated that the alloy possesses a compressive strength of ∼270 MPa and favourable plasticity. Nanoindentation results showed varying hardness and stiffness across the different phases. Notably, high hardness was observed for Sn3Bi, matrix, τ-Mg32(Zn,Al)49 phases respectively. Additionally, thermogravimetric examination demonstrated the alloy's exceptional oxidation resistance, maintaining stability in air up to temperatures as high as 490 °C.